Analisis Multi Kriteria Analisis Multi Kriteria Menggunakan Multi Attribute Utility Theory Dalam Seleksi Penerima Beasiswa - Fitri Handayani (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
Abstract Politeknik Kampar is a vocational college in Kampar Regency, Riau Province. Determination of scholarship recipients at universities is still manual and takes a long time to make the right decisions. These problems can be analyzed using the Multi Attribute Utility Theory (MAUT) decision support system method so that the decision-making process can be carried out more quickly. Where the analysis of the MAUT method is suitable for many criteria. The assessment criteria used consisted of 10 criteria including parental income, home ownership status, housing conditions, number of dependents, parental status, report cards, academic achievements, non-academic achievements, extracurricular activities and organizational experience with a total of 50 datasets. The research process consists of scientific literature, problem identification, data collection, MAUT method analysis, ranking and drawing conclusions. The results of research using the MAUT method can help the scholarship recipient selection team with a fast, effective and objective process in the decision-making process.